Analysis of the Influence of Marketing Mix and Store Layout on Purchase Decisions at Kimia Farma Pharmacy Central Jakarta Branch - Risma Werdaningsih; Wan Syurya Tri Dharma (Eduvest - Journal of Universal Studies, 2024)
In 2020, the Ministry of Health reported that there were 30,199 registered pharmacies (Ministry of Health of the Republic of Indonesia, 2022). This number fluctuated from 2018 to 2020, indicating competition in the pharmacy business. To face this competition, pharmacies need to implement strategies that can influence customers' purchasing decisions. This study aims to determine the influence of marketing mix and store layout on purchase decisions. The method used is quantitative with data collection through a Likert scale questionnaire. The number of samples was 100 respondents, calculated using the Yamane and Isaac-Michael formulas, and tested for validity and reliability using SPSS. The results of the multiple regression test show that the marketing mix and store layout together influence the purchase decision. This proved that both significantly influenced the purchase decision, so Ho was rejected and H1 was accepted. In addition, the test results also show that partially, these two factors have a significant influence on purchase decisions. The marketing mix strategy and store layout implemented by Kimia Farma's Central Jakarta branch is considered effective because it is able to influence purchasing decisions, as evidenced by the value of the R2 determination coefficient of 85.2%.